Consumption Risk and Expected Stock Returns - Parker, Jonathan A (American Economic Review, 2003)
U.S. stock returns are large, predictable over time, and predictable across stocks. The average return on a diversified market portfolio has averaged 8 percent per year more than the return on a short-term treasury bill. The predictability of time variation in returns is modest at high frequencies (about 10 percent of the variation in returns one quarter ahead is predictable) and quite large over longer periods (just under half of the variation in returns over five-year periods is predictable). Finally, portfolios based on the intersection of quintiles of stocks ranked by market value and by the ratio of book value to market value have differences in average annual returns across stocks of several percent per year. The natural explanation for these variations in returns is risk. But variations in consumption risk have done a poor job of explaining these differences in expected returns (see e.g., Sanford J. Grossman and Robert J. Shiller, 1981; Shiller, 1982; Lars Peter Hansen and Kenneth J. Singleton, 1983; N. Gregory Mankiw and Mat